DOA Estimation Based on Sparse Signal Recovery Utilizing Double-Threshold Sigmoid Penalty. (26th November 2015) - Wang, Hanbing; Li, Hui; Li, Bin
Abstract : This paper proposes a new algorithm based on sparse signal recovery for estimating the direction of arrival (DOA) of multiple sources. The problem model we build is about the sample covariance matrix fitting by unknown source powers. We enhance the sparsity by the double-threshold sigmoid penalty function which can approximate thel 0 norm accurately. Our method can distinguish closely spaced sources and does not need the knowledge of the number of the sources. In addition, our method can also perform well in low SNR. Besides, our method can handle more sources accurately than other methods. Simulations are done to certify the great performance of the proposed method.